High-Resolution 3D Reconstruction Reveals Intra-Synaptic Amyloid Fibrils - Capetillo-Zarate, Estibaliz (American Society for Investigative Pathology, 2011)
β-Amyloid (Aβ) accumulation and aggregation are hallmarks of Alzheimer's disease (AD). High-resolution three-dimensional (HR-3D) volumetric imaging allows for better analysis of fluorescence confocal microscopy and 3D visualization of Aβ pathology in brain. Early intraneuronal Aβ pathology was studied in AD transgenic mouse brains by HR-3D volumetric imaging. To better visualize and analyze the development of Aβ pathology, thioflavin S staining and immunofluorescence using antibodies against Aβ, fibrillar Aβ, and structural and synaptic neuronal proteins were performed in the brain tissue of Tg19959, wild-type, and Tg19959-YFP mice at different ages. Images obtained by confocal microscopy were reconstructed into three-dimensional volumetric datasets. Such volumetric imaging of CA1 hippocampus of AD transgenic mice showed intraneuronal onset of Aβ42 accumulation and fibrillization within cell bodies, neurites, and synapses before plaque formation. Notably, early fibrillar Aβ was evident within individual synaptic compartments, where it was associated with abnormal morphology. In dendrites, increasing intraneuronal thioflavin S correlated with decreases in neurofilament marker SMI32. Fibrillar Aβ aggregates could be seen piercing the cell membrane. These data support that Aβ fibrillization begins within AD vulnerable neurons, leading to disruption of cytoarchitecture and degeneration of spines and neurites. Thus, HR-3D volumetric image analysis allows for better visualization of intraneuronal Aβ pathology and provides new insights into plaque formation in AD.